O znaczeniu estetycznego ukształtowania przekazu w kontekście obrazy uczuć religijnych = Relationship between estetic shape of art and offense of religious feelings - Dąbrowska, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article deals with the image of religious feelings and the significance of the aesthetic level of artistic message in its perceiving. The subject included in the article of the analysis is the reception of the play "The Curse" directed by Olivier Frljic, whose examination allows to capture diverse attitudes accompanying the reception of artifacts affecting social spheres and taboos.
Keywords: estetyka; uczucia religijne; "Klątwa"; aestetics; religious feelings; "The Curse"